Perancangan Alat Penghitung Bibit Ikan Otomatis Dengan Metode Counter Berbasis Arduino - U S Sitorus Pane; M Yetri; A Pranata; F Rizky (Cered Indonesia Institute, 2021)
Fish and other aquatic animals are a source of protein for humans that are useful for building units in the biosynthesis of damaged human body parts and regulating and controlling body function metabolism. Automatic fish seed calculation aims to help fish cultivation to calculate the number of fish, as well as provide information on the results of the number of fish calculations. The Counter Up technique is a logical circuit that is used to count the input values in the input and output sections in the form of binary digits with a separate channel for each rank. The design system for the fish calculation system uses Arduino nano, one of the developments of a microcontroller that has a small size. The results of data testing carried out are in the form of servo motor rotation speed data, calculation counters and the maximum input power is 220 volts, the speed is 1300 rpm with a total of 468 calculation results. Fish seeds within 1 minute.